Stunting toddlers from vulnerable families in Pekanbaru City: findings feasible programs to reduce poverty - Atriana, Dinda (BKM Public Health and Community Medicine, 2021)
WHO ARE THE VICTIMS OF THIS INABILITY? Toddlers with stunting conditions in Pekanbaru City WHO AFFECTS THIS POWERFUL CONDITION? Communities with the majority of low family income fulfill their food needs as long as they are full even though they are poor in nutrition (1). WHAT CAUSES THIS CONDITION TO CONTINUE TO HAPPEN? Socio-economic conditions play an essential role in the incidence of stunting under five. In families with low incomes, the likelihood of experiencing nutritional problems such as stunting will be higher (2). Low income causes the most basic needs, namely food, which often cannot be met (1). So this is what triggers mothers to fulfill their food needs "merely" or as long as they are full even though they are poor in nutrition (1). Even with government assistance, the fulfillment of this nutrition is temporary. When the assistance provided has run out, the next food supply will remain "merely" because family income is still low. HOW POWERFUL ARE THE VICTIMS OF THIS CONDITION? The victims of this social condition are toddlers. The low family income impacts the lack of access to family food which results in difficulties to meet the nutritional adequacy of toddlers so that indirectly access to family food can affect the nutritional status of toddlers through the level of nutritional adequacy in toddlers (4). The quality and type of food given to toddlers and the feeding frequency are important factors related to the incidence of stunting in toddlers (3). CAN THIS POWERFULNESS BE OVERCOME? To overcome stunting in toddlers, it can be done by: Empowering families with low incomes (poor families) Expanding the Sustainable Food House Area (KRPL) (5) Creating a Continuity Of Care program that focuses on stunting toddlers Disseminating information about stunting through various media ( 5). Kondisi sosial ekonomi berperan penting terhadap kejadian stunting balita. Pada keluarga dengan pendapatan rendah, kemungkinan untuk mengalami kejadian masalah gizi seperti stunting akan lebih tinggi. Pendapatan rendah menyebabkan kebutuhan paling mendasar, yaitu pangan pun seringkali tidak bisa terpenuhi. Sehingga hal inilah yang memicu ibu-ibu untuk memenuhi kebutuhan pangan dengan “sekadarnya” atau asal kenyang padahal miskin gizi. Rendahnya pendapatan keluarga berdampak pada kurangnya akses pangan keluarga yang berakibat pada kesulitan untuk memenuhi kecukupan zat gizi balita, sehingga secara tidak langsung akses pangan keluarga dapat mempengaruhi status gizi balita melalui tingkat kecukupan zat gizi pada balita. Kualitas dan jenis makanan yang diberikan kepada balita serta frekuensi pemberian makanan merupakan faktor penting yang berkaitan dengan kejadian stunting pada balita.